The Leadership pocketbook a pocketful of tips and techniques for leaders at all levels--strategic, organisational and team level--on how to inspire, influence, deal with change and achieve objectives - Dent, Fiona Elsa (Management Pocketbooks, 2012)
This title explains how to inspire, influence, deal with change and achieve objectives. It adopts a practical approach, setting out the principles of leadership, the role of the leader, the skills required for effective leadership and the key challenges facing leaders in the current business environment.